2012
DOI: 10.1111/wej.12020
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phytoplankton composition in a Mediterranean coastal lagoon in the Cullera Estany (Comunitat Valenciana, Spain)

Abstract: The Cullera Estany is a coastal lagoon located in a highly intensified agriculture and tourist area in Valencia. This coastal lagoon has connections with the sea that produce marine intrusion and generate a freshwater interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
7
0
3
Order By: Relevance
“…In several temperate lagoons, seasonal distribution of phytoplankton groups was more strongly correlated with temperature than with salinity (Armi et al 2010, Pachés et al 2014. Our results resembled those of Melo et al (2007) for the tropical zone, where fluctuations in salinity and nutrient availability were the main drivers of phytoplankton community structure.…”
Section: Discussionsupporting
confidence: 72%
“…In several temperate lagoons, seasonal distribution of phytoplankton groups was more strongly correlated with temperature than with salinity (Armi et al 2010, Pachés et al 2014. Our results resembled those of Melo et al (2007) for the tropical zone, where fluctuations in salinity and nutrient availability were the main drivers of phytoplankton community structure.…”
Section: Discussionsupporting
confidence: 72%
“…The 504 phytoplankton dominance may be related to its strong capacity to compete for dissolved (Table 2). This phytoplankton functional group is tolerant to low 588 salinity as observed in freshwater and brackish coastal lagoons (Coelho et al, 2007;589 Cartaxana et al, 2009;Pachés et al, 2014) and is often observed in hypertrophic systems such 590…”
Section: Phytoplankton Chlorophyll Biomass In Heavily Eutrophied Lagomentioning
confidence: 99%
“…These particular physicochemical characteristics lead to a low chlorophyll a production not exceeding 5.84 μg.L -1 with an annual average of 2.41 μg.L -1 . These values are often low compared to several lagoons in the Mediterranean (Badosa et al, 2008;Roselli et al, 2009;Cañedo-Argüelles et al, 2012;Bernardi Aubry et al, 2013;Pachés et al, 2014). This physicochemical and hydrological situation is the result of a double effect.…”
Section: Discussionmentioning
confidence: 94%
“…) are often lower compared with ecosystems of neighboring countries including Bizerte lagoon in Tunisia (Sahraoui et al, 2009;Béjaoui et al, 2010) and Nador lagoon in Morocco (El-Madani et al, 2011). Overall Mellah lagoon waters are well oxygenated unlike some Mediterranean lagoons which are characterized by periodic dystrophy crisis when the dissolved oxygen can reach critical values (Lenzi et al 2003;Viaroli et al, 2006;Marinov et al, 2008;El Madani et al, 2011;Pachés et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation